Історія дослідження Амвросіївського верхньопалеолітичного комплексу - Кротова, О.О.; Сніжко, І.А. (Археологія, 2019)
Йдеться про історію відкриття та дослідження однієї з найважливіших верхньопалеолітичних епіграветських пам’яток України та Східної Європи, датується
18 000—19 000 некаліброваних років тому. Акцентується
увага на маловідомих фактах, що стосуються відкриття пам’ятки як палеонтологічного знаходища на початку ХХ ст. та як археологічного комплексу доби верхнього палеоліту у 1930-і роки. Наводяться біографічні дані
дослідників-першовідкривачів, аналізується їх роль у фіксації та збереженні інформації про пам’ятку. Представлено деякі недостатньо висвітлені у літературі дані, що
стосуються організації польових і лабораторних робіт
різних років досліджень та участі у них вітчизняних і
іноземних спеціалістів суміжних дисциплін, зокрема,
проведення на комплексі польового семінару радянськоамериканського симпозіуму «Upper Paleolithic — PaleoIndian Adaptations» (1989 р.) та його значення для інтерпретації пам’ятки. Амвросиевский верхнепалеолитический комплекс, который состоит из стоянки и костища бизонов расположен
на юго-востоке Украины вблизи г. Амвросиевка, в верховье балки Казенной. Вначале он был открыт геологами
в 1910-е гг. как скопление костей бизонов, которое позже в публикации детальной геологической карты района
было определено как палеонтологическое местонахождение природного происхождения (Мефферт 1923). Благодаря археологической разведке и раскопкам, проведенным в 1935 г. В. М. Евсеевым, научным сотрудником Сталинского ОМК, местонахождение стало известно как археологический, времени верхнего палеолита, памятник.
В 1940—1950 гг. стоянку и костище исследовала совместная экспедиция ИА АН УРСР и ИИМК АН СССР,
возглавляемая палеонтологом И. Г. Пидопличко и археологом П. И. Борисковским. Были определены характер
и основная площадь культурных отложений и собраны выразительные коллекции кремневых и костяных артефактов, предложены интерпретации костища как места загонной охоты и/или культового места охотников на
бизонов.
В 1980—2000 гг. исследования памятника продолжила экспедиция ИА НАНУ, возглавляемая А. А. Кротовой
при участии ряда отечественных и иностранных специалистов смежных наук: М. Ф. Веклича, Ж. Н. Матвийшиной, Н. П. Герасименко, Ю. Н. Грибченко, Е. И. Куренковой, Н. Г. Белан, В. Н. Логвиненко, А. В. Старкина,
Л. Тодда (США) и М.-А. Джулиен (Франция). В 1989 г. на памятнике был проведен полевой семинар согласно
программы советско-американского симпозиума «Upper Paleolithic—Paleo-Indian Adaptations», в работе которого
приняли участие известные ученые из США (О. Соффер, Л. Бинфорд, Д. Фризон, К. Хайнес, Б. Бредли, Д. Динкос, И. Адовасио, Л. Девис, Д. Мельтцер), Великобритании (К. Гембл), Украины и России. В результате исследований памятника была уточнена площадь распространения культурного слоя на костище и стоянке, собраны
новые, в том числе, оригинальные находки, дополнена интерпретация памятника как сложного комплекса охотников на бизонов на месте проведения неоднократных охотничьих операций и обитания вблизи него, на стоянке,
где проходили сложные хозяйственно-бытовые процессы. The Amvrosiivka Upper Palaeolithic complex, which consists of a site and bison bone bed, is situated in the SouthEast of Ukraine near Amvrosiivka city, in the upper reaches of the Kazenna ravine. In the beginning it was found by the
geologists in the 1910 as assemblage of bison bones, which was later determined in the detailed geologic map of the region
as paleontological seat of natural origin (Meffert 1923). Thanks to archaeological exploration and excavations, which were
held in 1935 by V. M. Evseev — the scholar of the Stalin Regional Museum of Local History, this location has come to notice
as Upper Palaeolithic archaeological site.
In 1940—1950-ies the site and the bone bed were studied by the collaborative expedition of IA AS USSR and IHMC AS
USSA, led by paleontologist I. H. Pidoplichko and archaeologist P. I. Boryskovskyi. Character and main area of cultural
stratum were defined; significant collection of flint and bone artifacts were collected; interpretations of the bone bed as a
place of battue and/or place of cult of bison hunters were proposed.
In 1980—2000-s the site research were continued by NASU Institute of Archaeology lead by O. O. Krotova with
the participation of the range of native and foreign specialists of allied sciences: M. F. Veklych, Zh. M. Matviishyna,
N. P. Herasymenko, Iu. M. Hrybchenko, O. I. Kurenkova, N. G. Belan, V. M. Lohvynenko, A. V. Starkin, L. Todd (USA)
and M.-A. Julien (France). In 1989 a field workshop was held on the site according to the program of the Soviet-American
“Upper Palaeolithic—Paleo-Indian Adaptations” symposium, in which famous scholars from the USA took part (O. Soffer,
L. Binford, D. Frizon, C. Haynes, B. Bradley, D. Dincauze, J. Adovasio, L. Davis, D. Meltzer) as well as scholars from
Great Britain (C. Gamble), Ukraine and Russia. As a result of the site research, the area of the bone bed and site cultural
layers was refined, new finds, including distinctive ones, were revealed, site interpretation was enlarged to be a compound
bison hunters complex on a place of holding repeated hunting operations and of dwelling nearit, on the site,where composite
domestic and household processes took place.